Development of Metacognition-Based LKPD to Improve Conceptual Understanding in Reaction Rate Material - Euis Nurmiati; Sugeng Bayu Wahyono; Muhammad Risal Rhomadan; Nurul Khairah; Ulfa Nabila Tafrienda (Jurnal Penelitian Pendidikan IPA, 2025)
The importance of constructivism-based chemistry learning is to develop students' conceptual understanding and metacognitive skills through active engagement, with the teacher as a facilitator, to create critical, independent, and globally competitive graduates. This study aims to develop Student Worksheets (LKPD) focused on metacognitive skills in learning reaction rate material, with the expectation of improving students' conceptual understanding and learning outcomes. Based on validation results, the LKPD has proven to be feasible for use, particularly in terms of language and metacognitive skills. In the first validation stage, the LKPD achieved an average percentage of 54.35%, which falls into the "feasible" category, while in the second stage, there was a significant improvement with an average percentage of 73.05%. Practicality assessments from teachers and students showed very good results, with teacher and student questionnaire scores ranging from 3.76 to 3.82 and 76.53% to 77.63%, respectively. Effectiveness evaluation through limited and wide trials indicated a significant improvement in conceptual understanding, with average posttest scores reaching the mastery category after using the metacognition-based LKPD. The improvement in conceptual understanding, calculated using the n-gain, showed a "moderate" category, with an average n-gain value of 0.60 for the limited trial and 0.63 for the wide trial. These results prove that the metacognition-based LKPD is effective in improving students' understanding and learning achievements in reaction rate material and can be used as an alternative in chemistry learning to develop students' higher-order thinking skills.